Application of Monte Carlo Simulation (MCS) and Fuzzy Finite Element (FFEM) for Investigating the Uncertainty of Seepage in Homogeneous Earth Dams - Milad Kheiry; Farhoud Kalateh (مجله مدل سازی در مهندسی)
In the analysis of saturated and semi-saturated soil media, the use of the finite element method results in more realistic analyses than deterministic methods due to the random nature of porous media properties. The purpose of this research is to investigate the impact of uncertainty in the prediction of seepage flow through earth dams using the Fuzzy Monte Carlo Simulation (FMCS) new hybrid algorithm, which is implemented with the help of the finite element method and monte carlo simulation. In this study, a computer program was used for Finite Element Analysis (FEA), which was definitively checked after validation with experimental results. Monte Carlo iteration loops were then used for probabilistic mode. The Fuzzy Finite Element Method (FFEM) was executed assuming the probability of the soil for four variables: soil permeability (Kx/Ky), water height ratio (Hd/Hu), horizontal width of downstream slope ratio to base width (Bd/B), and horizontal width of downstream slope ratio to horizontal upstream width (Bd/Bu). The results of this research show that the fuzzy membership function is linear-symmetric for Kx/Ky variables and linear-asymmetric for two geometric variables, Bd/B and Bd/Bu. Additionally, the membership function was extracted for Hd/Hu.